Quantum theory of the electron liquid - Giuliani, Gabriele F.; Vignale, Giovanni (Cambridge Cambridge University Press, 2005)
Modern electronic devices and novel materials derive extraordinary properties from the complex behavior of large numbers of electrons forming what is known as an electron liquid. This introduction to the physics of the interacting electron liquid covers a variety of systems, including metals, semiconductors, artificial nano-structures, atoms and molecules.
Keywords: Many-body problem; Quantum field theory; Fermi liquid theory; Fermi surfaces; Hartree-Fock approximation